2019
DOI: 10.1002/eap.1870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forestry‐driven changes to groundcover and soil moisture on amphibian desiccation, dispersal, and survival

Abstract: Over 80% of amphibian species that are declining are forest dependent. Forestry practices are a major cause of forest alterations globally, and it is well documented that clearcutting can contribute to amphibian declines. However, there might be adverse effects of forestry practices other than clearcutting. For example, planting overstory trees in rows (plantations) can change groundcover microhabitats and soil moisture levels, but the effects of this common practice on amphibian populations are not well studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Further work is needed to understand herpetofaunal population dynamics in working forests, as evidenced by the relatively low occupancy estimates we saw for many species and by the variation in responses shown by herpetofauna to specific effects of forest management activities in other studies (Rothermel and Luhring 2005, Todd and Andrews 2008, Haggerty et al 2019. Low occupancy estimates are a common feature of many reptile and amphibian species (Guzy et al 2019, Zipkin et al 2020), but it can be difficult to discern if low estimates are due to sampling methodology, interspecific interactions, unincorporated landscape variables, or naturally sparse populations.…”
Section: Discussionmentioning
confidence: 97%
“…Further work is needed to understand herpetofaunal population dynamics in working forests, as evidenced by the relatively low occupancy estimates we saw for many species and by the variation in responses shown by herpetofauna to specific effects of forest management activities in other studies (Rothermel and Luhring 2005, Todd and Andrews 2008, Haggerty et al 2019. Low occupancy estimates are a common feature of many reptile and amphibian species (Guzy et al 2019, Zipkin et al 2020), but it can be difficult to discern if low estimates are due to sampling methodology, interspecific interactions, unincorporated landscape variables, or naturally sparse populations.…”
Section: Discussionmentioning
confidence: 97%
“…We propose that even in the absence of water, features created by monsoon flows reduce the potential for desiccation and may provide important habitat for Chiricahua leopard frogs. Similarly, the understory composition of Florida pine plantations mediates the response of amphibians to drying, with Southern toads ( Anaxyrus terrestris ) experiencing greater desiccation risk in areas with less herbaceous groundcover and moving through more densely covered areas when available (Haggerty et al., 2019). Low‐lying cover could also provide some protection from predation.…”
Section: Discussionmentioning
confidence: 99%
“…Haggerty et al . (2019b) also found that amphibian desiccation was higher within intensive pine plantations compared to naturally regenerated stands, despite greater canopy cover. Historical disturbance may also cause long‐standing changes in ground‐layer structure and function that negatively impact amphibian populations (Burrow et al ., 2021).…”
Section: How Do Plants Affect Amphibians In Terrestrial Environments?mentioning
confidence: 92%
“…There have been relatively few attempts to demonstrate that vegetation drives the associated responses of amphibian species. Reduced groundcover vegetation in densely planted forest plantations in the southeastern USA has been linked to decreased amphibian larval occupancy and increased desiccation‐related mortality of juvenile amphibians (Haggerty, Crisman & Rohr, 2019a,b). Burrow, Crawford & Maerz (2021) also found that persistent reduced groundcover associated with historical agricultural use decreased juvenile frog survival in the presence of predatory ants.…”
Section: How Do Plants Influence Amphibian Distributions Abundance An...mentioning
confidence: 99%